2013
DOI: 10.1016/j.febslet.2013.05.067
|View full text |Cite
|
Sign up to set email alerts
|

Succinate receptor GPR91, a Gαi coupled receptor that increases intracellular calcium concentrations through PLCβ

Abstract: Edited by Lukas HuberKeywords: GPCR GPR91 Succinate PLCb PTX a b s t r a c t Succinate has been reported as the endogenous ligand for GPR91. In this study, succinate was confirmed to activate GPR91 resulting in both 3 0 -5 0 -cyclic adenosine monophosphate (cAMP) inhibition and inositol phosphate formation in a pertussis toxin (PTX)-sensitive manner. GPR91 agonist-mediated effects detected using dynamic mass redistribution (DMR) were inhibited with PTX, edelfosine and U73122 demonstrating the importance of not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 47 publications
4
43
0
1
Order By: Relevance
“…The view of SUCNR1 being coupled to G q has been later challenged. Sundstrom et al proposed that the [Ca 2+ ] i mobilization was a consequence of PLC-b activation by the dimer Gbg [41]. Our observation that SA elicits a concentration-dependent PTXsensitive [Ca 2+ ] i mobilization is consistent with SUCNR1 being not coupled to G q , at least when heterologously expressed in HEK293 cells.…”
Section: Discussionsupporting
confidence: 86%
“…The view of SUCNR1 being coupled to G q has been later challenged. Sundstrom et al proposed that the [Ca 2+ ] i mobilization was a consequence of PLC-b activation by the dimer Gbg [41]. Our observation that SA elicits a concentration-dependent PTXsensitive [Ca 2+ ] i mobilization is consistent with SUCNR1 being not coupled to G q , at least when heterologously expressed in HEK293 cells.…”
Section: Discussionsupporting
confidence: 86%
“…GPR91 and GPR99 are cell surface receptors and can be rapidly internalized like other GPCRs (12). A variety of intracellular signaling mechanisms—including inositol trisphosphate (IP 3 ) and Ca 2 + (12, 15), cAMP (13, 23), and mitogen-activated protein (MAP) kinases p38 and ERK1/2 (1517, 24)—have been linked to GPR91 and GPR99 activation via either the pertussis-toxin-sensitive G i /G o pathway or the pertussis-toxin-insensitive G q pathway (Figure 2). The detailed tissue distribution, signaling pathways, and (patho)physiological roles of GPR91 and GPR99 were recently reviewed (25, 26).…”
Section: Mitochondrial Citric Acid Cycle Intermediates and Their Gpcrsmentioning
confidence: 99%
“…Several authors repeatedly confirmed G i activation by demonstrating a decrease of cAMP levels upon succinate binding to SUCNR1 (Fig. 3), in both heterologous and native systems (Gilissen et al, 2015;Gnana-Prakasam et al, 2011 ;Hakak et al, 2009;Hogberg et al, 2011 ;Sundström et al, 2013). However, the view of SUCNR1 being coupled to G q has been challenged and it was proposed by several authors that the observed [Ca 2+ ] i mobilization was a consequence of PLC-β activation by the βγ dimer (Fig.…”
Section: Succinate Receptor 1 Signaling Pathwaysmentioning
confidence: 78%
“…However, the view of SUCNR1 being coupled to G q has been challenged and it was proposed by several authors that the observed [Ca 2+ ] i mobilization was a consequence of PLC-β activation by the βγ dimer (Fig. 3) (Gilissen et al, 2015;Sundström et al, 2013). The discrepancy between results may reflect distinct G protein partners among different cell types or artifacts induced by overexpression of the receptor.…”
Section: Succinate Receptor 1 Signaling Pathwaysmentioning
confidence: 99%